Insight and empathy: comparing the responses of pre-service teachers when reflecting on objective versus descriptive scenario-based learning. Issue 2 (4th March 2023) - Mead, Nadia
ABSTRACT: Stories build empathy and provide insights into character motivations and behaviour. When used in Initial Teacher Education programs, narratives can help pre-service teachers to examine conflict situations from an alternative perspective to their own. This paper shares the results of a qualitative pilot study conducted with pre-service teachers. Participants were asked to read short scenarios depicting two common conflict situations in educational settings: teacher and parent/carer conflict; and disruptive student behaviour. For each scenario, two versions were created. One version was constructed to mimic the kind of objective scenario common to Initial Teacher Education program study materials. The second version was created as a short story complete with characters, figurative language and dialogue. Participants were asked to read both versions of the same event, select their preferences and then explain their choices. The study analysed and thematically coded feedback between Primary and Secondary pre-service teachers. The results show mixed responses to both scenarios that represented a teacher's perspective of conflict with a parent/carer. In the case of a scenario about disruptive student behaviour, the results indicated a universal preference for the descriptive version. Participants empathised with the student perspective and valued the additional educational insights provided by the storied version.